Kangar Securities Sdn Bhd / Mohd Norkamarulezane Mohamad Zain ... [et al.] - Mohamad Zain, Mohd Norkamaruleazane; Ramli, Ahmad Rahimi; Mahzan, Helmi Azuan; Ahmad, Mishar (2001)
Kangar Securities Sdn. Bhd. is a new company that involves in the business world. It is a Stock Broking Company which to provide buying and selling of shares to clients. Beside that, Kangar Securities Sdn. Bhd. also may do some activities such as advise clients on possible investments, take orders from clients to buy or sell securities, execute transactions via WinSCORE (stock broking company front-end trading system), ensure payment is received from buying clients, ensure that when a client buys or sells shares all appropriate benefits low eg dividends, new issue and others.